2017
DOI: 10.1107/s2053230x17016831
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas syringae pv. actinidiae chemoreceptor protein F (PscF) periplasmic sensor domain: cloning, purification and X-ray crystallographic analysis

Abstract: Nitrate- and nitrite-sensing (NIT) domains are found associated with a wide variety of bacterial receptors, including chemoreceptors. However, the structure of a chemoreceptor-associated NIT domain has not yet been characterized. Recently, a chemoreceptor named PscF was identified from the plant pathogen Pseudomonas syringae pv. actinidiae that is predicted to contain a periplasmic NIT domain. The PscF sensor domain (PscF-SD; residues 42-332) was cloned into an appropriate expression vector, recombinantly prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Unique NIT (PF08376) domains ( Oulavallickal et al, 2017 ), containing cyclases, were previously identified in Trichoplax ( Moroz et al, 2020 ) as candidates for nitrite/nitrate sensors, similar to bacteria ( Shu et al, 2003 ; Camargo et al, 2007 ). Mnemiopsis has one sequence (ML02033a) associated with the same cluster ( Figure 5 ) but with a highly derived NIT-like region and unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…Unique NIT (PF08376) domains ( Oulavallickal et al, 2017 ), containing cyclases, were previously identified in Trichoplax ( Moroz et al, 2020 ) as candidates for nitrite/nitrate sensors, similar to bacteria ( Shu et al, 2003 ; Camargo et al, 2007 ). Mnemiopsis has one sequence (ML02033a) associated with the same cluster ( Figure 5 ) but with a highly derived NIT-like region and unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…This pathway frequently works together with the gaseous nitric oxide (NO)-mediated signaling machinery in chemosensory and neuronal processes (30,31). Further genomic deciphering of these NO-dependent pathways and, in particular, the quest for NO-reception complement, led to the discovery and identification of very unusual guanylate cyclases with unique nitrate-and nitrite-sensing (NIT) domains (32) in the lobster genome. These NIT domains were previously characterized in prokaryotes (e.g., bacteria and cyanobacteria) (33).…”
Section: B Amentioning
confidence: 99%
“…Unexpectedly, we discovered 12 additional guanylate cyclases with unique NIT domains 76 , which were only previously known from bacteria as nitrate and nitrite sensors 77 , 78 . Nitrate/nitrite sensing type domain in placozoans (NIT: PF08376) is flanked by two transmembrane domains and a C-terminal guanylate cyclase catalytic domain (AC/GC: PF00211).…”
Section: Resultsmentioning
confidence: 91%